The Role of Financial Literacy in Supporting Employee Work-Life Balance - Bancoro, Jaysone Christopher; Barillo, Reli Maria; Buhian , Dee Laila (Journal of Interdisciplinary Perspectives, 2025)
Balancing work and family responsibilities is a significant challenge for employees in today's dynamic workplace. Financial literacy empowers employees to manage finances effectively, reducing stress and improving focus. It fosters better decision-making, enhances financial security, and promotes a healthier work-life balance. This study examines how financial literacy influences employees' work-life balance by mitigating financial stress and supporting well-being, job satisfaction, and effectiveness. Utilizing a correlational descriptive design, quantitative and qualitative data were collected from 140 and 8 faculty members and staff, respectively, from different colleges in one state university through surveys and interviews to analyze the relationship between financial literacy and work-life balance. Results indicate that employees have financial literacy, with an average score on knowledge at 8.35 (SD = 3.13), positive attitudes (M = 3.99, SD = 0.73), and positive financial behaviors (M = 3.94, SD = 0.58). Qualitative findings indicate that employees have acknowledged the relevance of financial planning tools but may have problems with complex financial ideas and a form of hesitancy about long-term financial goals. Correlation analysis revealed a weak association between financial literacy and work-life balance (rho = 0.11) and was not statistically significant (p = 0.191). Despite work-life balance policies, challenges related to heavy workloads, financial pressure, and limited personal time remain. These results indicate that targeted financial education programs and increased workplace flexibility are required to reduce stress and support employee well- being.